An Investigation into the Impact of Information on Stock Price Volatilities in Vietnam - Nguyen, Huu Huy Nhut (University of Economics Ho Chi Minh City, 2023)
Based on the panel data of 22 stock tickers in the two porfolios VN30 and HNX30 during 2008–2014, the research empirically investigates the impact of information on stock price volatilities in Vietnam. Non-traditional data collection approach and OLS and GARCH (1;1) models, along the use of data on information supply measured by the number of disclosures of the studied stocks and data on information demand measured by the number of search attempts on Google by means of Google Trend allow the research findings to be distilled into clear recommendations, which show that: (i) Both information supply and demand do affect stock price volatilities; and (ii) More profound and significant impact has been produced by information demand; particularly, effects of market-level information demand are more powerful than those of stock-level information demand.